Learning Chemical Bonds in Terms of Identifying Difficulties, Misconceptions, Learning Media, and Learning Models: A Systematic Literature Review - Faira Yovanie (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine and describe the identification of difficulties, misconceptions, learning media, and learning models on chemical bonds. The method used in this research is the systematic literature review method. Article search results starting from 2014 to 2024 were selected gradually and systematically. The results of this research show that students' difficulties and misconceptions can be minimized by applying learning models and media. It is evident from several articles studied that they are able to answer research questions, namely: How to identify difficulties in chemical bonds among students? what are the misconceptions that occur in chemical bonds? What are the appropriate learning models for chemical bonds? and What are the appropriate learning media for chemical bonds? The results and findings in several articles show that difficulties and misconceptions in chemical bonds can be minimized by applying learning models and media to reduce misconceptions about chemical bonds.